Annelid Fauna of the Prince Gustav Channel, a Previously Ice-Covered Seaway on the Northeastern Antarctic Peninsula - Drennan, Regan; Dahlgren, Thomas G.; Linse, Katrin; Glover, Adrian G. (Frontiers in Marine Science, 2021)
The Prince Gustav Channel is a narrow seaway located in the western Weddell Sea on the northeastern-most tip of the Antarctic Peninsula. The channel is notable for both its deep (>1200m) basins, and a dynamic glacial history that most recently includes the break-up of the Prince Gustav Ice shelf, which covered the southern portion of the channel until its collapse in 1995. However, the channel remains mostly unsampled, with very little known about its benthic biology. We present a preliminary account of the benthic annelid fauna of the Prince Gustav Channel in addition to samples from Duse Bay, a sheltered, glacier-influenced embayment in the northeastern portion of the channel. Samples were collected using an Agassiz Trawl, targeting megafaunal and large macrofaunal sized animals at depths ranging between 200–1200m; the seafloor and associated fauna were also documented in situ using a Shallow Underwater Camera System (SUCS). Sample sites varied in terms of depth, substrate type, and current regime, and communities were locally variable across sites in terms of richness, abundance, and both taxonomic and functional composition. The most diverse family included the motile predator/scavenger Polynoidae, with 105 individuals in at least 12 morphospecies, primarily from a single site. This study provides first insights into diverse and spatially heterogeneous benthic communities in a dynamic habitat with continuing glacial influence, filling sampling gaps in a poorly studied region of the Southern Ocean at direct risk from climate change. These specimens will also be utilized in future molecular investigations, both in terms of describing the genetic biodiversity of this site and as part of wider phylogeographic and population genetic analyses assessing the connectivity, evolutionary origins, and demographic history of annelid fauna in the region.